STUDI KASUS TENTANG PESERTA DIDIK YANG SERING MEMBOLOS DI SMP NEGERI 7 SUNGAI RAYA - Jelisti Utami; Yuline Yuline; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThis research aims to reveal about the relief efforts that will be given to learners at SMP Negeri 7 Sungai Raya who often ditch. Method used was descriptive in form survey .The conclusion of this research is, in know that the characteristic of case subject is in three consecutive week not entering school without permission, the subject of the case has been through the process of guidance, the parent / guardian of the case subject has been through the process of calling and coming too late. Factors causing factors is the fear of being late and feeling lazy because it was not school in the previous day. The counseling model used to help the case subject is the REBT counseling model. The result of the change is that within a month the subject of the case is absent. The researcher's suggestion is that case subjects are expected to maintain and improve again the positive changes they have.Keywords: Case study, Trainee, Truant